Report of the Committee to Identify 100 Most Backward and Poorest District in the Country - Ministry of Rural Areas and Employment, Government of India (Ministry of Rural Areas and Employment, Government of India, 1997)
This report presents the findings of a committee constituted in 1997 to identify the 100 most backward and poorest districts in India, in line with the Common Minimum Programme’s objective of formulating a Special Action Plan for rural infrastructure development. The committee, comprising experts from the Planning Commission, academia, and government ministries, was tasked with developing appropriate criteria, identifying eligible districts, and defining the scope of infrastructure development. Recognising the unique developmental challenges of the North Eastern states and Jammu & Kashmir, the committee excluded them from the exercise to allow for separate, focused strategies. The report undertakes a comprehensive review of earlier approaches to defining backwardness, including studies by various committees and planning bodies, which relied on a combination of economic, social, and infrastructural indicators such as per capita income, employment structure, agricultural productivity, industrial development, literacy, health facilities, and transport connectivity. Emphasis is placed on district-level analysis due to data availability and administrative relevance. The report highlights that backwardness is a multidimensional concept requiring the integration of poverty, resource utilisation, infrastructure deficits, and human development indicators. By synthesising past methodologies and refining criteria, the committee aims to ensure a more objective and targeted identification of districts most in need of intervention, thereby enabling focused policy measures to reduce regional disparities and promote inclusive rural development.
Ministry of Rural Areas and Employment, Government of India
Ministry of Rural Areas and Employment, Government of India
Keywords: Backward Districts Identification, Rural Infrastructure Development, Poverty Indicators, Planning Commission, Regional Imbalance, Economic Criteria, Industrial Development, Agricultural Productivity, Social Indicators, Committee Report 1997, District-Level Analysis, Development Planning